Understanding Mesoscale Aggregation of Shallow Cumulus Convection Using Large‐Eddy Simulation - C. S. Bretherton; P. N. Blossey (Journal of Advances in Modeling Earth Systems)
Abstract Marine shallow cumulus convection, often mixed with thin stratocumulus, is commonly aggregated into mesoscale patches. The mechanism and conditions supporting this aggregation are elucidated using 36 h large‐eddy simulations (LES) on a 128 × 128 km doubly periodic domain, using climatological summertime forcings for a location southeast of Hawaii. Within 12 h, mesoscale patches of higher humidity, more vigorous cumulus convection, and thin detrained cloud at the trade inversion base develop spontaneously. Mesoscale 16 × 16 km subdomains are composited into quartiles of column total water path and their heat and moisture budgets analyzed. The weak temperature gradient approximation is used to explain how apparent heating perturbations drive simulated mesoscale circulations, which in turn induce relative moistening of the moistest subdomains, a form of gross moist instability. Self‐aggregation is affected by precipitation and mesoscale feedbacks of radiative and surface fluxes but still occurs without them. In that minimal‐physics setting, the humidity budget analysis suggests self‐aggregation is more likely if horizontal‐mean humidity is a concave function of the horizontal‐mean virtual potential temperature, a condition favored by radiative cooling and cold advection within the boundary layer.